자율형 분석심사 선도사업의 효과평가 연구 - 이은해; Eun Hae Lee; 윤석준; Seok-jun Yoon; 허륜; Ryun Hur; 최민재; Minjae Choi; 이요한; Yo Han Lee (HIRA Research, 2024)
Background: This study evaluated the Autonomous Analysis and Review Pilot Project within the Health Insurance Review & Assessment Service, focusing on its efficiency and potential for improvement. The fee-for-service model increases medical utilization, necessitating balanced reviews to ensure appropriate care. To address this concern, an autonomous analysis and review system that enabled healthcare institutions to manage care quality and costs using data-driven analysis, particularly in specialized medical fields, was introduced. Methods: This study assessed changes in healthcare quality and efficiency using indicators such as healthcare quality metrics, claim amounts, and hospitalization days. A control group was established to which participating and non-participating institutions were compared before and after the system’s implementation. The analytical methods included the ARIMA (autoregressive integrated moving average) model, propensity score matching, and difference-in-differences for time series analysis, comparative analysis, and quantitative evaluation, respectively. Results: For stroke, healthcare quality indicators―such as imaging test rates, anticoagulant prescription rates, rehabilitation assessment rates, and 30-day mortality rates―showed positive changes after implementation, though statistical significance was limited. Efficiency indicators, including average medical cost per patient and length of stay, exhibited a decreasing trend. In cases of severe trauma, significant reductions in average medical cost per patient and length of stay were observed, along with improved efficiency metrics. Conclusion: The pilot project showed potential for improving healthcare quality and efficiency. Our results suggest that the autonomous analysis and review system enables healthcare institutions to effectively manage healthcare quality and resource expenditure. Nonetheless, further studies with extended durations and more participating institutions are needed for a precise evaluation.